2005
DOI: 10.1128/iai.73.11.7495-7501.2005
|View full text |Cite
|
Sign up to set email alerts
|

Murine Macrophages Kill the Vegetative Form of Bacillus anthracis

Abstract: Anti-protective antigen antibody was reported to enhance macrophage killing of ingested Bacillus anthracis spores, but it was unclear whether the antibody-mediated macrophage killing mechanism was directed against the spore itself or the vegetative form emerging from the ingested and germinating spore. To address this question, we compared the killing of germination-proficient (gp) and germination-deficient (⌬gerH) Sterne 34F2 strain spores by murine peritoneal macrophages. While macrophages similarly ingested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 36 publications
5
141
0
Order By: Relevance
“…We report here that treatment targeting B. anthracis bacilli to phagocytes by enzymatically removing the capsule can protect animals from infection, further supporting the role of capsule in evading host innate immunity. Although dormant spores may not be susceptible to phagocytic killing until they germinate (17,20,32), the vegetative form of the organism is susceptible to phagocytic killing, particularly when devoid of capsule (20,28,39,42). As mentioned above, enzyme treatment to remove microbial capsules has been successfully used to treat existing infections with pneumococci, Cryptococcus, and E. coli (2,15,31) in mouse models of infection.…”
Section: Discussionmentioning
confidence: 99%
“…We report here that treatment targeting B. anthracis bacilli to phagocytes by enzymatically removing the capsule can protect animals from infection, further supporting the role of capsule in evading host innate immunity. Although dormant spores may not be susceptible to phagocytic killing until they germinate (17,20,32), the vegetative form of the organism is susceptible to phagocytic killing, particularly when devoid of capsule (20,28,39,42). As mentioned above, enzyme treatment to remove microbial capsules has been successfully used to treat existing infections with pneumococci, Cryptococcus, and E. coli (2,15,31) in mouse models of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports had suggested that the GerX, GerH, and to a lesser extent the GerS receptors, are important for the establishment of anthrax infection and disease progression (Guidi-Rontani et al, 1999;Ireland and Hanna, 2002b;Kang et al, 2005;. However, recent data shows that as long as one of the genomically encoded receptors (GerH, GerK, GerL, or GerS) is present, B. anthracis spores remain fully virulent in an inhalational anthrax murine model (Carr et al, 2010).…”
Section: Bacillus Anthracis Ger Receptorsmentioning
confidence: 85%
“…Peritoneal fluid was drawn through the abdominal wall with a 23-gauge needle. Fluid from mice was pooled, washed, total cell counts determined using a hemacytometer, and the remaining fluid was centrifuged at 380×g for 10 min at 4 o C (Kang et al, 2005). Washed cell suspensions were adjusted to 10 6 macrophages per ml in culture medium containing RPMI-1640 with fetal bovine serum (FBS) 10% and 50 μg/ml gentamicin, and incubated in 24-well cell culture plate in 5% CO2 at 37 o C overnight before exposure to HS.…”
Section: Preparation Of Murine Peritoneal Macrophages and Culturementioning
confidence: 99%